A bibliometric analysis of synaptic plasticity and epilepsy from 2003 to 2023 - Li, Xuewei; Sun, Huaiyu; Chen, Zhiqing; Meng, Hongmei; Zhang, Daguang (Frontiers in Neurology, 2025)
Background and purposeEpilepsy is a prevalent and chronic neurological disorder. Recent studies suggest that synaptic plasticity could be a promising therapeutic target for epilepsy. This research employed bibliometric techniques to assess the study trends of synaptic plasticity in epilepsy over the last 20 years, highlighting major areas of focus and new topics.MethodsResearch articles on synaptic plasticity in epilepsy, spanning 2003 to 2023, were sourced from the Web of Science Core Collection (WoSCC) database. Tools including CiteSpace, VOSviewer, and various online bibliometric platforms were utilized to conduct a deeper analysis of the collected data.ResultsFrom 2003 to 2023, a total of 1,060 publications related to synaptic plasticity in epilepsy were indexed, including 309 review articles. Over the past two decades, both the number of publications and their citations have increased. The United States emerged as the leading country in terms of the number of both review and original research articles published, highlighting its significant influence in this field. Among all authors, Fabio Benfenati was the most cited in review articles, while Xuefeng Wang was the most cited in original research articles. Over the past 20 years, Frontiers in Cellular Neuroscience published the highest number of review articles on synaptic plasticity in epilepsy, while The Journal of Neuroscience published the most original research articles on this topic.ConclusionThis research examined 1,369 studies on synaptic plasticity in epilepsy and highlighted the prevailing trends in the field. The research findings indicate that the current focus of review studies is on gamma-aminobutyric acid, amyloid beta peptide, and glutamate receptors, while the focus of original research is on astrocytes, NMDA receptors, and long-term potentiation.